The Mediator Role of Job Satisfaction between Social Support and Employees ‘Performance at Saudi Ports Authority - Saud Mira, Mohammed; Voon Choon, Yap; Kok Thim, Chan; Yauri, Harunaaliyu (International Journal of Psychosocial Rehabilitation, 2020)
Human resource department is a core department in any organization. It puts into consideration the key factors of employee relationships and social support. Social support depends heavily on employee relationships. Employee performance and job satisfaction are key determinants of organizational output.